RpoN Promotes Pseudomonas aeruginosa Survival in the Presence of Tobramycin - Viducic, Darija; Murakami, Keiji; Amoh, Takashi; Ono, Tsuneko; Miyake, Yoichiro (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa has developed diverse strategies to respond and adapt to antibiotic stress. Among the factors that modulate survival in the presence of antibiotics, alternative sigma factors play an important role. Here, we demonstrate that the alternative sigma factor RpoN (σ54) promotes survival in the presence of tobramycin. The tobramycin-sensitive phenotype of logarithmic phase ΔrpoN mutant cells is suppressed by the loss of the alternative sigma factor RpoS. Transcriptional analysis indicated that RpoN positively regulates the expression of RsmA, an RNA-binding protein, in the P. aeruginosa stationary growth phase in a nutrient-rich medium. The loss of RpoS led to the upregulation of gacA expression in the nutrient-limited medium-grown stationary phase cells. Conversely, in the logarithmic growth phase, the ΔrpoS mutant demonstrated lower expression of gacA, underscoring a regulatory role of RpoS for GacA. Supplementation of tobramycin to stationary phase ΔrpoN mutant cells grown in nutrient-rich medium resulted in decreased expression of gacA, relA, and rpoS without altering the expression of rsmA relative to wild-type PAO1. The observed downregulation of gacA and relA in the ΔrpoN mutant in the presence of tobramycin could be reversed through the mutation of rpoS in the ΔrpoN mutant background. The tobramycin-tolerant phenotype of the ΔrpoNΔrpoS mutant logarithmic phase cells may be associated with the expression of relA, which remained unresponsive upon addition of tobramycin. The logarithmic phase ΔrpoS and ΔrpoNΔrpoS mutant cells demonstrated increased expression of gacA in response to tobramycin. Together, these results suggest that a complex regulatory interaction between RpoN, RpoS, the Gac/Rsm pathway, and RelA modulates the P. aeruginosa response to tobramycin.